2012
DOI: 10.1080/00423114.2011.645489
|View full text |Cite
|
Sign up to set email alerts
|

Inverse neuro-fuzzy MR damper model and its application in vibration control of vehicle suspension system

Abstract: In this paper, a magneto-rheological (MR) damper-based semi-active controller for vehicle suspension is developed. This system consists of a linear quadratic Gauss (LQG) controller as the system controller and an adaptive neuro-fuzzy inference system (ANFIS) inverse model as the damper controller. First, a modified Bouc-Wen model is proposed to characterise the forward dynamic characteristics of the MR damper based on the experimental data. Then, an inverse MR damper model is built using ANFIS technique to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 18 publications
0
59
0
1
Order By: Relevance
“…This model can accurately capture both the force-displacement and force-velocity hysteresis loops, which involve as many as 14 parameters. In contrast, Kamath and Wereley [120] developed an augmented six-parameter model to accurately describe both the force-displacement and force-velocity hysteresis cycles, which was constructed using a nonlinear combination of linear mechanisms. Choi and Lee [83] proposed the damper model shown in Fig.…”
Section: Dampersmentioning
confidence: 97%
See 1 more Smart Citation
“…This model can accurately capture both the force-displacement and force-velocity hysteresis loops, which involve as many as 14 parameters. In contrast, Kamath and Wereley [120] developed an augmented six-parameter model to accurately describe both the force-displacement and force-velocity hysteresis cycles, which was constructed using a nonlinear combination of linear mechanisms. Choi and Lee [83] proposed the damper model shown in Fig.…”
Section: Dampersmentioning
confidence: 97%
“…Several models were proposed to characterize the performance of the MR damper [82,119,120]. Spencer et al [121] proposed a modified Bouc-Wen model to describe the MR damper behavior.…”
Section: Dampersmentioning
confidence: 99%
“…Simulation results showed that the vibration reduction performance of self-tuning fuzzy logic controller is best compared to uncontrolled and Fuzzy Logic controlled suspension systems. Recently, many control strategies have been developed and evaluated for their practical applicability in semi-active suspension system, which includes H-infinity control [18], fuzzy hybrids [19], hybrid sliding mode control [20], LQG control [21] and adaptive neuro fuzzy hybrid control [22], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks (NN) have been effectively applied to model complex systems due to their good learning capability. Zong et al (2012) propose an adaptive neuro-fuzzy inference system (ANFIS) inverse model to determine the input current so as to gain the desired damping force. Simulation results demonstrate that the desired force can be accurately tracked using the ANFIS technique.…”
Section: Introductionmentioning
confidence: 99%